2021
DOI: 10.1038/s41598-021-86433-6
|View full text |Cite
|
Sign up to set email alerts
|

Diquafosol tetrasodium elicits total cholesterol release from rabbit meibomian gland cells via P2Y2 purinergic receptor signalling

Abstract: Diquafosol tetrasodium (DQS), a purinergic P2Y2 receptor agonist, stimulates secretion of both water and mucins from the conjunctiva into tears. Hence, DQS-containing eye drops have been approved as a therapeutic option for dry eye disease in some Asian countries, including Japan. Recent clinical reports state that instilling DQS-containing eye drops significantly increases the lipid layer thickness in tears. Therefore, we examined this compound’s direct actions on holocrine lipid-secreting meibomian gland cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…To our knowledge, only the previous study of our research performed in healthy rabbits evaluated tear break-up time after a treatment containing dinucleotides, where there were no changes with the extract of 4% Artemia salina [ 30 ]. On the other hand, different studies demonstrated that the activation of the P2Y 2 receptor by topical instillation of Up 4 U stimulates the production of mucins and lipids in the Goblet cells and Meibomian glands, respectively [ 15 , 16 , 34 , 35 ]. Considering that mucins and lipids are the responsible components for tear film stability [ 36 ], the possibility that the artificial tears with Artemia salina improves this stability in future clinical studies should not be discarded based on the hypothesis that the Gp4G present in the crustacean could act as an agonist of P2Y 2 receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only the previous study of our research performed in healthy rabbits evaluated tear break-up time after a treatment containing dinucleotides, where there were no changes with the extract of 4% Artemia salina [ 30 ]. On the other hand, different studies demonstrated that the activation of the P2Y 2 receptor by topical instillation of Up 4 U stimulates the production of mucins and lipids in the Goblet cells and Meibomian glands, respectively [ 15 , 16 , 34 , 35 ]. Considering that mucins and lipids are the responsible components for tear film stability [ 36 ], the possibility that the artificial tears with Artemia salina improves this stability in future clinical studies should not be discarded based on the hypothesis that the Gp4G present in the crustacean could act as an agonist of P2Y 2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…On the ocular surface, P2Y 2 receptor has been described in the cornea, conjunctiva, and lacrimal gland [ 10 ]. The activation of P2Y 2 receptor via topical instillation of diadenosine tetraphosphate (Ap 4 A) and diuridine tetraphosphate (Up 4 U) demonstrated its capability to stimulate aqueous [ 11 , 12 , 13 , 14 ], mucinous [ 15 ], and lipidic [ 16 ] components of tears, as well as to accelerate corneal re-epithelization [ 15 , 17 , 18 ]. Additionally, the instillation of these compounds increases the corneal permeability [ 19 , 20 ] and the levels of both lysozyme [ 21 ] and lactoferrin [ 22 ] in tears.…”
Section: Introductionmentioning
confidence: 99%
“…It has achieved positive results in basic and clinical research in the field of DE. The diquafosol tetrasodium (DQS) was found to stimulate meibocytes to release lipids through the P2Y2 receptor and possibly facilitate holocrine secretion in isolated rabbit Meibomian gland cells ( 96 ). Diquafosol significantly reduced the levels of reactive oxygen species, apoptosis, and inflammation in corneal cells caused by DE in in vivo and in vitro DE models ( 97 ).…”
Section: Purine and Purinergic Receptors And Dementioning
confidence: 99%
“…As recently reported, 3% diquafosol tetrasodium ophthalmic solution (Diquas ® , DQS), a P2Y2 receptor agonist that acts on goblet cells, corneal and conjunctival epithelium, and meibomian glands, can promote tear fluid, mucin, and lipid secretion and help epithelium repair ( 12 , 13 ). Several clinical trials have shown that DQS significantly reduces corneal and conjunctival staining, prolongs tear breakup time (TBUT), increases Schirmer test score and improves subjective symptoms in patients with dry eye ( 14 17 ).…”
Section: Introductionmentioning
confidence: 99%